LEGAL STATUS OF WARSHIP WRECKS FROM WORLD WAR II IN INDONESIAN TERRITORIAL WATERS (INCIDENT OF H.M.A.S. PERTH COMMERCIAL SALVAGING) - Meskin, Senada (Faculty of Law, Universitas Brawijaya, 2015)
Second World War was one of the most devastating experiences that World as a whole had to endure. The war left so many issues unhandled, one such issue is the theme of this thesis, and that is to analyze legal regime that is governing sunken warships. Status of warship still in service is protected by international law and national law of flag State, stipulating that warships are entitled on sovereign immunity. The question rises whether or not such sovereign immunity status follows warship wreck? Contemporary international law regulates very little considering ‘sovereign wrecks’, but customary international law, municipal court decisions and State practices are addressing issue quite profoundly, stating that even the warship is no longer in service it is still entitled on sovereign immunity status. HMAS Perth is Australian owned warship whose wreck current location is within Indonesian Territorial Sea. Recent reports show that commercial salvaging has been done, provoking outrage amongst surviving HMAS Perth’s naval personnel and Australian historians. In order to acquire clear stand point on issue of Sovereign Wrecks legal status, especially of HMAS Perth’s wreck, an in-depth analysis of legal material is necessary.Keywords: Territorial Waters, Warship, Warship Wreck, Salvage